Examining the Fit of the Psychological Well-Being Model of Adolescents Based on Early Maladaptive Schemas with the Mediation of Emotion Regulation - Khanizadeh, Roja; Taghvaei, Davood; Zanganeh Motlagh, Firoozeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Adolescence brings about new changes in the psychological system, including thinking and planning for the future, evaluating alternatives, introspection, reasoning, abstract thinking, new levels of autonomy and assertiveness, and generally new cognitive abilities. Methods and Materials: This study aimed to examine the fit of the psychological well-being model of adolescents based on early maladaptive schemas with the mediation of emotion regulation. The research design was applied in nature, using a descriptive-correlational method with a structural modeling approach. The statistical population of this study included all adolescents studying in the second period of secondary schools in Tehran during the academic year 2020-2021. The sample consisted of 400 individuals selected from the research population using cluster sampling. The tools used in this study included the Psychological Well-Being Questionnaire (Ryff, 1989), the Young Schema Questionnaire-Short Form (Young, 1994), and the Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004). For data analysis in descriptive statistics, SPSS-24 software was used, and for inferential statistical analysis to test hypotheses and confirm or reject them, the structural equation modeling (SEM) method with AMOS-22 software was employed. Findings: The findings indicated that, according to the chi-square and RMSEA criteria, the model provided a good fit for the data regarding the psychological well-being of adolescents based on early maladaptive schemas with the mediation of emotion regulation. Conclusion: Emotion regulation serves as a mediator between psychological well-being and early maladaptive schemas, meaning that early maladaptive schemas can indirectly enhance psychological well-being by reducing emotional dysregulation.